The issue of microplastic in the oceans: Preferences and willingness to pay to tackle the issue in Australia. (January 2022) - Borriello, Antonio; Rose, John M.
Abstract: Microplastic is becoming a more and more tangible problem worldwide. Wildlife, including fish of any size, ingests tiny particles of plastic that may end up in human bodies via food chain. While literature still debates on the potential harm to humans, it is evident that microplastic is damaging the marine ecosystem. Policy makers around the world have the duty to reduce, if not to eliminate, microplastic pollution on beaches and oceans. Many countries, including Australia, have moved first steps in this direction, however the challenge remains enormous. At present, there exists no market to reveal the preferences for reducing microplastic in the world's oceans, nor to determine whether people are willing to play a role in such a reduction. This research investigates the preferences for management policies tackling the issue of microplastic in the ocean off New South Wales (Australia) by means of a stated preference experiment. Findings suggest that residents of NSW would support policies that focus on microplastic pollution reduction and would be willing to contribute financially paying a yearly household levy. Via a latent class model, the paper supports policy makers by providing information specific to different clusters within the population, identifying three segments with preferences spanning from "very caring of the marine environment" to "not caring at all of the marine environment". Highlights: There is little knowledge around preferences for reducing microplastic pollution. Three quarters of the sample would approve policies pro-reduction of microplastic. Residents of NSW are willing to pay a levy to reduce microplastic pollution. Preferences can be clustered in three segments ranging from pro- to indifferent.